Civil service, HR potential, and open innovation - A. G. Polyakova (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Countries strive to upgrade their civil service quality in many directions, thus responding to major contemporary challenges and following the trends of open innovation. The 2030 civil servant will require a wide set of soft and hard skills that are not common among the today's public administrators but are attributable to young people. The following questions then arise: Will the demand for qualified civil servants be reduced because of optimization of public administration processes? How significant is the demand for young people by the civil service? Is civil service attractive as a vector of career development among young people? The research objective is to provide quantity estimates of the Russian civil service's hiring potential and to match that potential with young people's attitude towards public administration employment. Using the panel regression, regions that can expand the civil service staff were identified and the necessary preconditions and policies to take use of this potential were indicated. The main conclusion is that governments should maintain incentives to join the civil service and improve the image of civil service among the youth to make it an attractive employer.
Keywords: 650; civil service; human resources potential; labor market; open social innovation; panel regression; public administration; social network analysis; young people